Antimicrobial peptides for treatment of patients with herpes virus-associated chronic prostatitis - E. V. Kulchavenya; S. Yu. Shevchenko; A. A. Baranchukova (Вестник урологии, 2023)
Introduction. Genital herpes is a chronic sexually transmitted infection characterised by recurrent self-limiting genital ulcers caused by herpes simplex virus type 1 (HSV-1) or type 2 (HSV-2) and can be associated with chronic prostatitis (CP).Objective. To determine the efficacy of cytokines-antimicrobial peptides complex in therapy of patients with herpes virus-associated chronic prostatitis.Materials & methods. The pilot, open, prospective, non-comparative study included 23 patients who were followed up for CP for a mean of 9.7 ± 4.2 years. All were diagnosed with abacterial CP / chronic pelvic pain syndrome (CPPS) with signs of inflammation and detection of HSV DNA in urethral swabs by polymerase chain reaction (PCR). Prescribed therapy: Tab. Valaciclovir 500 mg b.i.d. p.o. for 10 days, Tab. Ketoprofen 100 mg q.d. for 5 days, Supp. Superlymph 10 IU q.d. p.r. q.h.s. for 20 days. The results were evaluated at the end of therapy, 3 and 6 months after its completion.Results. At the end of therapy, the leukocytes count in prostate secretion decreased by almost five times and remained stable throughout the entire follow-up period. The total symptom scale score at the end of therapy decreased from 22.96 ± 6.01 to 6.61 ± 3.71 points (p < 0.05). There was also a change in the perception of pain on a visual analog scale. If, before the start of treatment, 14 patients (60.9%) assessed the pain intensity as “severe” and only two (8.7%) had “weak” pain intensity, then after the end of therapy, none of the patients had severe pain, 21 (91.3%) patients noted "mild" pain and in 2 patients (8.7%) the intensity of pain was regarded as "average". Quality of life improved from baseline 8.23 ± 1.91 points to 2.43 ± 1.41 points immediately after completion of therapy (p < 0.05). Three months after therapy, patients assessed the quality of life as 2.43 ± 1.41 points, and six months later, as 2.81 ± 1.21 points. During the first three months, one patient experienced a HPV-relapse; one more — within the next three months. These patients underwent a second course according to a similar scheme. None of the patients reported significant side effects on any component of the therapeutic complex.Conclusion. In abacterial CP/CPPS, a herpes infection should be identified. Being neurotropic, HSV can cause / exacerbate the pain characteristic of CP/CPPS. In case of persistent pain, HSV infection should be excluded. In the treatment of patients with herpes virus-associated abacterial CP, Supp. Superlymph showed good immediate and long-term results.